2017
DOI: 10.1037/fam0000265
|View full text |Cite
|
Sign up to set email alerts
|

When stress gets into your head: Socioeconomic risk, executive functions, and maternal sensitivity across childrearing contexts.

Abstract: Socioeconomic adversity has been targeted as a key upstream mechanism with robust pathogenic effects on maternal caregiving. Although research has demonstrated the negative repercussions of socioeconomic difficulties, little research has documented potential mechanisms underlying this association. Toward increasing understanding, the present study examined how maternal working memory capacity and inhibitory control may mediate associations between socioeconomic risk and change in maternal sensitivity across fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 70 publications
5
45
0
Order By: Relevance
“…And now, an emerging line of research is investigating the link between EFs and parenting, across a variety of different EFs, and in relation to both harsh and positive parenting behaviours (see Crandall et al, 2015 for review). For example, Sturge-Apple, Jones, and Suor (2017) demonstrate direct links between mothers' EFs (assessed by working memory and inhibitory control) and how sensitively they respond to their child's behaviour measured observationally. Given that parenting places demands on parents' emotional and cognitive resources, it makes sense that EFs are helpful in allowing parents to navigate parenting situations successfully.…”
Section: Executive Functions and Harsh Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…And now, an emerging line of research is investigating the link between EFs and parenting, across a variety of different EFs, and in relation to both harsh and positive parenting behaviours (see Crandall et al, 2015 for review). For example, Sturge-Apple, Jones, and Suor (2017) demonstrate direct links between mothers' EFs (assessed by working memory and inhibitory control) and how sensitively they respond to their child's behaviour measured observationally. Given that parenting places demands on parents' emotional and cognitive resources, it makes sense that EFs are helpful in allowing parents to navigate parenting situations successfully.…”
Section: Executive Functions and Harsh Parentingmentioning
confidence: 99%
“…In the current study, I have chosen to examine EFs that reflect the themes of this most recent study. Because much of the previous literature has focused on working memory in association to parenting (e.g., Deater-Deckard, Sewell, Petrill, & Thompson, 2010;Sturge-Apple et al, 2014;Sturge-Apple et al, 2017), I aimed to extend the research by examining cognitive flexibility in association with parenting. In addition, to represent the overall unified EF construct, I included a measure of problem-solving skills, which is defined as a higher-level EF involving other EF skills, such as working memory and cognitive flexibility, working together in a collaborative fashion (Karr et al, 2018).…”
Section: Executive Functions and Harsh Parentingmentioning
confidence: 99%
“…Previous studies have found that cognitive flexibility is impaired in individuals with SUD (Cunha et al, ). In addition, impairments in cognitive flexibility are associated with a heightened experience of stress in parents (Sturge‐Apple, Jones, & Suor, ) and with emotion dysregulation in women with SUD (Marceau et al, ). Mothers with young children and mothers with SUD are shown to have a readily activated “hot” EF system (i.e., EF “coloured” by emotion) when faced with distress (Gladwin & Figner, ; Gonzalez, ; Volkow & Baler, ).…”
Section: Discussionmentioning
confidence: 99%
“…Parenting practices, including MR, depend in great extent of cognitive control, subserved by executive functions with a limited capacity (Crandall et al, 2015 ). Cognitive control can be decreased due to executive dysfunction associated with maternal attention deficit hyperactive disorder (ADHD) or due to stressful situations (Crandall et al, 2015 ; Sturge-Apple et al, 2017 ). The presence of multiple young children at the same time is a source of stress due to limited resources and also a significant challenge to cognitive control abilities (Salmon, 2005 ).…”
Section: Discussionmentioning
confidence: 99%